2018
DOI: 10.3897/natureconservation.24.20538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-fire logging on California spotted owl occupancy

Abstract: In fire-adapted forest ecosystems around the world, there has been growing concern about adverse impacts of post-fire logging on native biodiversity and ecological processes. This is also true in conifer forests of California, U.S.A. which are home to a rare and declining owl subspecies, the California spotted owl (Strix occidentalis occidentalis). While there has been recent concern about the California spotted owl occupancy in large fire areas where some territories have substantial high-severity fire effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…This large fire occurred partly within the boundary of our long-term, demographic study area containing individually-marked California spotted owls. In addition, we (Jones et al 2016) found no effect of salvage logging on the owls, but Hanson et al (2018) claimed that the negative effects of the King Fire on spotted owls was due to salvage logging, not severe fire. Therefore, we developed this paper for two reasons.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…This large fire occurred partly within the boundary of our long-term, demographic study area containing individually-marked California spotted owls. In addition, we (Jones et al 2016) found no effect of salvage logging on the owls, but Hanson et al (2018) claimed that the negative effects of the King Fire on spotted owls was due to salvage logging, not severe fire. Therefore, we developed this paper for two reasons.…”
Section: Introductionmentioning
confidence: 82%
“…Regarding the second question, while there is unanimous empirical support that predominately low-severity fires have little negative impact on owls (Bond et al 2002, Bond 2016, Ganey et al 2017, there are two general alternative findings about the effect of large, high-severity fires on owls: neutral/beneficial effects (e.g. Bond et al 2009Bond et al , 2016Lee et al 2012;Lee and Bond 2015;Hanson et al 2018) and negative effects (Comfort et al 2016;Jones et al 2016;Eyes et al 2017;Ganey et al 2017;Rockweit et al 2017) (see also below the section "The science of spotted owls and fire"). Determining which of these results is correct will influence how forest restoration proceeds within the range of the spotted owl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Hanson et al. ). Because Spotted Owl studies typically characterize territory vegetation only in the breeding core area within 1.1 km of the nest, these studies ignore habitat changes and alterations in the year‐round home‐range area that can extend up to 5.9 km from the nest (Zabel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Post-fire logging is likely to be partially responsible for some of the negative effects attributed to high-severity fire in the studies reviewed here (Tempel et al 2014, Jones et al 2016, Rockweit et al 2017, Hanson et al 2018. Because Spotted Owl studies typically characterize territory vegetation only in the breeding core area within 1.1 km of the nest, these studies ignore habitat changes and alterations in the year-round home-range area that can extend up to 5.9 km from the nest (Zabel et al 1992).…”
Section: Discussionmentioning
confidence: 99%